2010
DOI: 10.1177/1474022209349767
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Lecturer and Student Accounts of Reading in the Humanities

Abstract: This article reports the outcomes of an exploratory small-scale study to compare lecturer and student conceptions of critical reading at a research-intensive UK institution. Analysis of lecturer and student interviews in four humanities subjects suggests differences in the way lecturers and students conceptualize and articulate the practices of critical reading. Lecturers conceptualize reading as creative and intertextual, a defamilarization of personal experiences of the world and the development of relationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…This suggests that researchers do not consider reading to be a methodological practice significantly influencing the knowledge they produce. Thus, although reading is recognized as a core academic skill (Brookman and Horn, 2016; Culler, 2010; Love, 2010; Maclellan, 1997; Weed, 2012; Weller, 2010), it is by implication constructed as a supplement to genuine research methods. To our knowledge, research undertaken specifically to identify how reading informs and influences knowledge production processes, as well as to develop a conception of reading as a method of inquiry in its own right, is lacking.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that researchers do not consider reading to be a methodological practice significantly influencing the knowledge they produce. Thus, although reading is recognized as a core academic skill (Brookman and Horn, 2016; Culler, 2010; Love, 2010; Maclellan, 1997; Weed, 2012; Weller, 2010), it is by implication constructed as a supplement to genuine research methods. To our knowledge, research undertaken specifically to identify how reading informs and influences knowledge production processes, as well as to develop a conception of reading as a method of inquiry in its own right, is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Within the field of higher education, studies on student approaches to reading assert that these are often instrumental and framed as information-seeking practices aimed at comprehension (Douglas et al., 2016; Stokes and Martin, 2008; Tomasek, 2009; Weller, 2010: 89). Furthermore, reading practices are associated with a generic study skills agenda (Weller, 2010: 89) that is said to be ineffective, misleading and counterproductive to learning (Wingate, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…And if this is the case, we might conclude that students enter the humanities not to “engage in learning about the human” (Mora), but to engage in learning about learning – as active participants in a communal process that many of them will continue as educators themselves. We can better serve these many students who are drawn to careers in education by foregrounding, and involving them more self‐consciously in understanding, the methods and practices we wish them to learn, rather than, as we currently do, modeling those practices and expecting them to become transparent (Weller).…”
mentioning
confidence: 99%
“…However, counter to this principle, one study found lecturers in humanities conceptualized critical reading very differently from their students. 41 Therefore, this leads to an area for further study within both disciplines.…”
Section: Discussionmentioning
confidence: 99%